Organizing for transformation? How and why organizers plan their multi-stakeholder forums - Sarmiento Barletti, J.P.; Larson, A.M.; Heise Vigil, N. (2021)
Multi-stakeholder forums (MSFs) have received much attention from policymakers and development and conservation practitioners as a transformative solution for more equitable coordination and decision-making over environmental challenges. Studies on “invited spaces” have previously shown the importance of balancing power relations and attending to context. To what extent do the plans and expectations of MSF organizers reflect these previous lessons? This article examines how and why the organizers of 13 subnational MSFs addressing sustainable land and resource management in Brazil, Ethiopia, Indonesia and Peru established these forums, and if and how their plans and expectations compare to previous lessons on invited spaces. Findings reveal that the organizers conceived of power inequalities as obstacles that could be overcome by including historically disempowered peoples in the MSFs, but generally failed to consider specific measures to address inequalities; nor did they develop clear strategies to engage with unsustainable local development and political priorities.